Use of bluff body for enhancing submicron particle agglomeration in plasma field - Asanakham A. (2017)
2016 Copyright © Taylor & Francis Group, LLC A bluff body was installed to generate a vortex shedding in gas flow under nonthermal plasma field. Various shapes of bluff body were analyzed using computational fluid dynamics for their ability to enhance submicron particle agglomeration. The cylindrical bluff body produced the lowest pressure drop and the plate bluff body showed the widest amplitude of vortex shedding. In the experiment, exhaust gas with a velocity of 1–3 m/s were fed into the test section. The electrical pulse peak voltage was 35 kV, 10 kHz. The bluff body improved the reduction efficiency by 27% and 17% for flat plate and cylindrical bluff bodies, respectively, relative to no-bluff body.